Application value of MRI-based 3D reconstruction technology in laparoscopic D3 radical resection of rectal cancer with pelvic autonomic nerve preservation - CHEN Jiajia, KE Yingping, GUO Weiyi, YANG Xi, YE Haixuan, HONG Jianwen (Xin yixue, 2024)
Objective To evaluate the application value of the MRI-based three-dimensional （3D） reconstruction of pelvic autonomous nerves and surrounding organs in laparoscopic D3 radical resection for rectal cancer. Methods Fifty-six patients with rectal cancer were randomly divided into the reconstruction and control groups. In the reconstruction group， surgical plans were formulated based on preoperative MRI 3D reconstruction. In the control group， conventional surgical plans were formulated. Intraoperative and postoperative functional recovery-related indicators were compared between two groups. Results The 3D reconstruction model provided individualized visualization of the distribution relationship between the pelvic autonomous nerves and surrounding organs. Compared to the control group， patients in the reconstruction group had significantly shorter operation time （（143.7±13.3）min vs. （151.5±12.1） min， P = 0.040）， less blood loss （（31.3±12.1） mL vs. （39.4±11.6） mL， P = 0.024））， improved IPSS score （（6.0±1.3） vs. （7.9±2.6）， P = 0.003）， and shorter duration of urinary catheter removal （2.0（2.0， 2.0）d vs. 3.5（3.0， 4.0）d， P < 0.001）. Conclusions MRI-based 3D reconstruction of pelvic autonomous nerves provides a more precise visualization of the anatomical position of the pelvic autonomous nerves and surrounding organs， ultimately improving the efficiency and safety of D3 resection. It offers important reference for surgeons in formulating precise and individualized surgical plans.